Differential Responses of Polyamines and Antioxidants to Drought in a Centipedegrass Mutant in Comparison to Its Wild Type Plants - Liu, Mingxi; Chen, Jingjing; Guo, Zhenfei; Lu, Shaoyun (Frontiers in Plant Science, 2017)
Centipedegrass (Eremochloa ophiuroides [Munro] Hack.) is an important warm-season turfgrass species with low turf maintenance requirements. However, our knowledge on physiological adaptation of centipedegrass to drought stress is limited. Physiological responses to drought in a gamma-ray-induced mutant 22-1 as compared with two wild type (WT) lines were analyzed for understanding of drought tolerance mechanism of centipedegrass. The mutant showed an elevated drought tolerance with higher levels of relative water content (RWC), net photosynthetic rate (A) and stomatal conductance (gs) and lower levels of ion leakage and malondialdehyde (MDA) under drought stress as compared with WT plants. A showed significant correlation with gs and MDA. Higher levels of antioxidant enzymes activities, non-enzyme antioxidants, and polyamines including putrescine (Put), spermidine (Spd), and spermine (Spm) were maintained in 22-1 than in WT plants. Superoxide dismutase (SOD), catalase (CAT), ascorbate-peroxidase (APX), and glutathione reductase (GR) activities and ascorbic acid (AsA) content were significantly correlated with both Put and Spd levels, and reduced glutathione (GSH) level was correlated with Put during drought stress. Exogenous application of Put, Spd, and Spm increased drought tolerance and activities of SOD, CAT, APX, and GR in WT plants. The results suggest that higher levels of polyamines and antioxidant defense system are associated with the elevated drought tolerance in 22-1, which may improve protection on photosynthesis against drought induced oxidative damage.